Above‐ground and below‐ground responses to long‐term nutrient addition across a retrogressive chronosequence. (29th December 2015) - Wardle, David A.; Jonsson, Micael; Mayor, Jordan R.; Metcalfe, Daniel B.
Summary: There is much interest in understanding ecosystem responses to local‐scale soil fertility variation, which has often been studied using retrogressive chronosequences that span thousands of years and show declining fertility and plant productivity over time. There have been few attempts to experimentally test how plant nutrient limitation changes during retrogression. We studied a well‐characterized system of 30 forested lake islands in northern Sweden that collectively represent a 5350‐year post‐fire retrogressive chronosequence, with fertility and productivity decreasing as time since fire increases. For each island, we set up four plots on understorey vegetation, each subjected to a different fertilizer treatment over 6 years: no additions, nitrogen (N) only, phosphorus (P) only and N + P. We found that both N and P additions reduced feather moss and thus total plant biomass. Meanwhile, the three dominant vascular plant species showed contrasting biomass responses, but similar responses of foliar nutrient concentrations to nutrient additions. Fertilization reduced most microbial groups and altered CO2 fluxes, most likely through feather moss reduction. Against expectations, the majority of interactive effects of N and P were antagonistic. Changes in effects of nutrient additions during retrogression were usually modest. Empetrum hermaphroditum biomass was increasingly promoted by P and N + P addition, while vascular plant N‐to‐P ratios were increasingly reduced by P addition, indicating increasing plant limitation by nutrients (notably P) during retrogression. Below‐ground, positive effects of N addition on soil mineral N increased, while negative effects of N addition on soil fungi decreased during retrogression; no other below‐ground effects of fertilization changed along the gradient. Synthesis . Our results show that forest understorey communities on islands of different fire history and thus stages of retrogression show relatively modest differences in how they respond to nutrient addition despite large changes in ecosystem productivity and soil fertility, probably because of high species turnover and adaptation of communities to infertile conditions. While increased nutrient availability (as expected through global change) may have important ecological consequences, these effects are likely, especially below‐ground, to be rather similar across ecosystems that differ greatly in nutrient availability and productivity. Abstract : Our results show that forest understorey communities on islands of different fire history and thus stages of retrogression show relatively modest differences in how they respond to nutrient addition despite large changes in ecosystem productivity and soil fertility, probably because of high species turnover and adaptation of communities to infertile conditions. While increased nutrient availability (as expected through global change) may have important ecological consequences, these effects are likely, especially below‐ground, to be rather similar across ecosystems that differ greatly in nutrient availability and productivity.